AWAL TERJADINYA KORUPSI (STUDI KASUS KORUPSI OLEH PENYELEGGARA NEGARA ) - Isnawati Isnawati (Prodi Ilmu Administrasi Negara, 2015)
ABSTRACTThis research is a library research by local newspaper namely Tribun Kaltim dan Kaltimpost .It was held in 2014 .The focus is about corruption in Banten , Sangatta and Jakarta. The corruption in Banten is about the dynasti of Atut , The corruption in Sangatta is the state officers and the corruption in Jakarta is the head of the Democrat political party.The method of the research is to select the corruption news published by the newspaper concerned.The result of it is that the corruption can be happened because of three conditions namely : opportunity , willing and power.In Banten Ratu Atut as a governor,in Sangatta as state – officers of the regency and Anas Urbaningrum as the chairman of the Democrat Political Party have those three reason mentioned above.The suggestions of the resarcher to avoid of the corruption criminal action are to keep the opportunity , willing and power in honest ways .It means a man cannot use those three reasons to be out of control.